Analysis on Band Layer Design and J-V characteristics of Zinc Oxide Based Junction Field Effect Transistor - Ms Chaw Su Nandar Hlaing; Thiri Nwe (Newinera Publisher, 2020)
This paper presents the band gap design and J-V characteristic curve of Zinc Oxide (ZnO) based on Junction Field Effect Transistor (JFET). The physical properties for analysis of semiconductor field effect transistor play a vital role in semiconductor measurements to obtain the high-performance devices. The main objective of this research is to design and analyse the band diagram design of semiconductor materials which are used for high performance junction field effect transistor. In this paper, the fundamental theory of semiconductors, the electrical properties analysis and bandgap design of materials for junction field effect transistor are described. Firstly, the energy bandgaps are performed based on the existing mathematical equations and the required parameters depending on the specified semiconductor material. Secondly, the J-V characteristic curves of semiconductor material are discussed in this paper. In order to achieve the current-voltage characteristic for specific junction field effect transistor, numerical values of each parameter which are included in analysis are defined and then these resultant values are predicted for the performance of junction field effect transistors. The computerized analyses have also mentioned in this paper.